Clitics in Brazil: literary demand through Jorge Amado - Vázquez, Ignacio (Revista de Filología Románica, 2012)
From a syntactic perspective, the position of object pronouns in Portuguese speech today offers two possibilities: the European use (compulsory in Africa and Asia) and the American one. What began as a linguistic difference between Portugal and Brazil became a national issue. Dignifying that difference in writing -especially in literature- meant emancipation for the former colony (Brazil). Brazilian writer Jorge Amado helped to achieve this.